Organization of Judicial Administration and Management during the Buyid and Seljuk Rule : between the years (334-447 AH/945-1055/447-590 AH/1055-1191 AD) - Hoshmand Bapir Othman; Ako Burhan Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research is entitled (Organization of Judicial Administration and Management during the Buyid and Seljuk Rule between the years (334-447 AH/945-1055/447-590 AH/1055-1191 AD) in Iraq and Iran. This study introduces us to the system of governance and administration of both powers and presents their management, by highlighting the system of governance and judicial administration and presenting the different aspects of their management. This study emphasizes the linguistic and terminological introduction of the judiciary, as well as the ceremonies of their appointment, election conditions and judicial affairs. It analyses the responsibilities of the judiciary during both the Buyid and Seljuk rule in terms of their salaries, rewards and judicial duties. The study method is comparative and analytical.